Analysis of Environmental Literacy Skills Based on Hands-on Activities (HoA) of Muhammadiyah 16 Surabaya Elementary School Students - fauzi, Muchammad; Binti Mirnawati, Lilik; Dian Ayu Alfiani, Kunti (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this research is to ascertain an analysis of environmental literacy skills based on Hands-on Activities (HoA) among Muhammadiyah 16 Surabaya Elementary School students. By employing the Hands-on Activity (HoA) method in this learning activity, children can engage in a pleasant and non-boring manner. The research method employed for this study is qualitative-descriptive, utilizing data collection techniques such as observation, interviews, documentation, and audio-visual methods. Data analysis involves descriptive techniques such as data reduction, data display, and data verification. Furthermore, data validity is ensured through triangulation techniques. The research findings can be concluded that the Hands-on Activity (HoA) learning method has a significant impact on students' environmental awareness, promoting their ongoing commitment to environmental conservation and sustainability. Through the HoA teaching approach, students are encouraged to directly identify elements within their environment, recording the names of local regions and the Latin names of plants found around the school vicinity. The HoA method underscores a constructivist learning approach, placing more emphasis on student-centered learning where students are directly engaged in observing real-life phenomena or situations.